Dosimetric feasibility of computed tomography-based image-guided brachytherapy in locally advanced cervical cancer: a Japanese prospective multi-institutional study. (3rd February 2021) - Otani, Yuki; Ohno, Tatsuya; Ando, Ken; Murata, Kazutoshi; Kato, Shingo; Noda, Shin-ei; Murofushi, Keiko; Ushijima, Hiroki; Yoshida, Daisaku; Okonogi, Noriyuki; Isohashi, Fumiaki; Wakatsuki, Masaru; et al.
ABSTRACT: The aim of this study was to assess the feasibility of planning dose–volume histogram (DVH) parameters in computed tomography-based 3D image-guided brachytherapy for locally advanced cervical cancer. In a prospective multi-institutional study, 60 patients with stage IIA2–IVA cervical cancer from eight institutions were treated with external beam radiotherapy using central shielding and intracavitary or hybrid (combined intracavitary/interstitial) brachytherapy (HBT). The dose constraints were set as a cumulative linear quadratic equivalent dose (EQD2) of at least 60 Gy for high-risk clinical target volume (HR-CTV) D90, D2cc ≤ 75 Gy for rectum, D2cc ≤ 90 Gy for bladder and D2cc ≤ 75 Gy for sigmoid. The median HR-CTV D90 was 70.0 Gy (range, 62.8–83.7 Gy) in EQD2. The median D2cc of rectum, bladder and sigmoid was 57.1 Gy (range, 39.8–72.1 Gy), 68.9 Gy (range, 46.5–84.9 Gy) and 57.2 Gy (range, 39.2–71.2 Gy) in EQD2, respectively. In 76 of 233 sessions (33%), 23 patients underwent HBT, and the median number of interstitial needles was 2 (range, 1–5). HBT for a bulky HR-CTV (≥40 cm 3 ) significantly improved the HR-CTV D90 compared with intracavitary brachytherapy alone ( P = 0.010). All patients fulfilled the dose constrains for target and at risk organs by undergoing HBT in one-third of sessions. We conclude that the planning DVH parameters used in our protocol are clinically feasible.